Electrospun vascular grafts fabricated from poly(L-lactide-co-ε-caprolactone) used as a bypass for the rabbit carotid artery. (20th September 2018) - Horakova, Jana; Mikes, Petr; Lukas, David; Saman, Ales; Jencova, Vera; Klapstova, Andrea; Svarcova, Tereza; Ackermann, Michal; Novotny, Vit; Kalab, Martin; Lonsky, Vladimir; Bartos, Marin; et al.
Abstract: The study involved the electrospinning of the copolymer poly( L -lactide-co- ε -caprolactone) (PLCL) into tubular grafts. The subsequent material characterization, including micro-computed tomography analysis, revealed a level of porosity of around 70%, with pore sizes of 9.34 ± 0.19 μ m and fiber diameters of 5.58 ± 0.10 μ m. Unlike fibrous polycaprolactone, the electrospun PLCL copolymer promoted fibroblast and endothelial cell adhesion and proliferation in vitro . Moreover, the regeneration of the vessel wall was detected following implantation and, after six months, the endothelialization of the lumen and the infiltration of arranged smooth muscle cells producing collagen was observed. However, the degradation rate was found to be accelerated in the rabbit animal model. The study was conducted under conditions that reflected the clinical requirements—the prostheses were sutured in the end-to-side fashion and the long-term end point of prosthesis healing was assessed. The regeneration of the vessel wall in terms of endothelialization, smooth cell infiltration and the presence of collagen fibers was observed after six months in vivo . A part of the grafts failed due to the rapid degradation rate of the PLCL copolymer.